Optogenetic Inhibition of the Subthalamic Nucleus Reduces Levodopa-Induced Dyskinesias in a Rat Model of Parkinson's Disease - Yoon, Hyung Ho; Min, Joongkee; Hwang, Eunmi; Lee, C. Justin; Suh, Jun-Kyo Francis; Hwang, Onyou; Jeon, Sang Ryong (KARGER, 2016)
Background: The inhibition of neuronal activity by electrical deep brain stimulation is one of the mechanisms explaining the amelioration of levodopa-induced dyskinesia. However, electrical deep brain stimulation cannot specifically activate or inactivate selected types of neurons. Objectives: We applied optogenetics as an alternative treatment to deep brain stimulation for levodopa-induced dyskinesia, and also to confirm that the mechanism of levodopa-induced dyskinesia amelioration by subthalamic nucleus deep brain stimulation is mediated through neuronal inhibition. Methods: 6-hydroxydopamine-induced hemiparkinsonian rats received injections of hSynapsin1-NpHR-YFP adeno-associated virus (AAV) or hSynapsinl-YFP AAV. Two weeks after viral injections, all rats were treated with daily injections of levodopa. Then, the optic fiber was implanted into the ipsilateral subthalamic nucleus. We performed various behavioral tests to evaluate the changes in levodopa-induced dyskinesias after optogenetic expression and illumination in the subthalamic nucleus. Results: The behavioral tests revealed that optical inhibition of the subthalamic nucleus significantly ameliorated levodopa-induced dyskinesia by reducing the duration of the dyskinesias as well as the severity of axial dyskinesia. Conclusions: These findings will provide a useful foundation for the future development of optogenetic modulation systems that could be considered as an approach to dyskinesia therapy. (C) 2016 S. Karger AG, Basel
Keywords: HIGH-FREQUENCY STIMULATION; DEEP BRAIN-STIMULATION; BASAL GANGLIA; REPLACEMENT; MECHANISMS; AKINESIA; CORTEX